The Development of English Story Book in Student Speaking Skills - Dwi Nur Hadiyansah WS; Virgania Afifah Fajaria (Lembaga Pengembangan Kinerja Dosen, 2025)
The aims of this research are not only to know the development of English Storybook in Students speaking skill of Al-Qomar Institute but also to know the advisability of English Storybook in students speaking skill of Al-Qomar Institute Giri Banyuwangi. Researcher utilized the development of Sugiyono method with eight stages. The stages included: (1) Potential and Problem, (2) Collection of Data, (3) Product Design, (4) Design Validation, (5) Design Revision, (6) Product Trial, (7) Product Revision, and (8) Final product. In the previous study, the researcher used VOS viewer to get the references which conducted with the title of the research. The information collecting through interview, questionnaire, documentation and test. The data collecting through used four validators. They are validator of design expert, validator of content expert, teacher perception, and student’s respondent. The product user is the member of Institute of ala-Qomar Giri Banyuwangi which consisted of 24 students. The result showed: 1) the process includes: a) the design of English Storybook development step, b) the expert of English Storybook and the validation of the assessment step from the expert, teacher perception and student respond. 2) The validity level of English Storybook is obtained based on the result of contain expert is 90%, the score was categorized as “very good” with interval 80% < x < 100%, design expert is 86%, the score was categorized “verry good” with interval 80% < x < 100%, teacher perception is 97%, the score was categorized “very good” with interval 80% < x < 100%, and student respond is 87%, the score was categorized “very good” with interval 80% < x < 100%. So, it can be seen that the criteria of validation level are very valid and not revision. This English storybook that has been revised by design expert and contain expert. This English storybook can be used a reference by teachers to try to improve the student speaking skills and can be some learning media is appropriate to the student’s condition. It means, that used English storybook is very positive for the students. Keywords:English Storybook, Speaking Skill, How to cite